A New MRI-Based Model of Heart Function with Coupled Hemodynamics and Application to Normal and Diseased Canine Left Ventricles - Choi, Young Joon; Constantino, Jason; Vedula, Vijay; Trayanova, Natalia; Mittal, Rajat (Frontiers in Bioengineering and Biotechnology, 2015)
A methodology for the simulation of heart function that combines an MRI-based model of cardiac electromechanics (CE) with a Navier-Stokes based hemodynamics (NSH) model is presented. The cardiac electromechanics model consists of two coupled components that simulate the electrical and the mechanical functions of the heart. Accurate representations of ventricular geometry and fiber orientations are constructed from the structural magnetic resonance and the diffusion tensor MR images, respectively. The deformation of the ventricle obtained from the electromechanical model serves as input to the hemodynamics model in this one-way coupled approach via imposed kinematic wall-velocity boundary conditions and at the same time, governs the blood flow into and out of the ventricular volume. The time-dependent endocardial surfaces are registered using a diffeomorphic mapping algorithm while the intraventricular blood flow patterns are simulated using a sharp-interface immersed boundary method based flow solver. The utility of the combined heart function model is demonstrated by comparing the hemodynamic characteristics of a normal canine heart beating in sinus rhythm (SR) against that of the dyssynchronously-beating failing heart. We also discuss the potential of coupled cardiac electromechanics and hemodynamics models for various clinical applications.